Auxílio Emergencial - Lessons from the Brazilian experience responding to COVID-19 : Summary Note - Lara De Arruda, Pedro; Lazarotto de Andrade, Marina; Falcão, Tiago; Teixeira Barbosa, Diana; Morgandi, Matteo (World Bank, Washington, DC, 2022)
The Auxílio Emergencial (AE) was one of the most agile, robust, and extensive social protection programs implemented by developing countries. Having reached up to 55.6 percent of the population, considering both direct and indirect beneficiaries, the program has shown impacts in improving the average income and reducing the prevalence of poverty and inequality (as measured by the Gini index1 ), compared to immediate pre-pandemic levels. The success of the program can be attributed both to its robustness and to its complex architecture, marked by innovations which should be analyzed by their integration potential in relation to regular social protection policies and measures to increase adaptation to the social protection system, both in Brazil and in other countries.